How Does The Quality of Work Life Affect The Commitment of Health Workers? - Antayamulya, Vianesa Aurum; Sari, Risqi Adinda; Ernawaty, Ernawaty; Puspitasari, Nur Alifa Hera; Putri, Nuzulul Kusuma (Unnes Journal of Public Health, 2024)
Human resources has become the most important thing during the COVID-19 pandemic because COVID-19 affects the health worker not only physically but also mentally. Thus, it is important to continuously improve the Quality of Work Life (QWL) to maintain the health worker wellbeing during this tough time. This sudy aimed to examine the QWL of health workers who work at the Puskesmas and to find the association between QWL and work commitment. This research was a quantitative type of research using an observational analytic. The population of this research was all health center personnel in East Java with a minimum number of 267 respondents. The independent variable in this study is QWL and the dependent variable is the commitment of health workers. Data collection was done by distributing an online questionnaire. The results of this study indicated that the health workers of Puskesmas in East Java had a high commitment in handling COVID-19 and their QWL was sufficient. The ordinal regression test showed that QWL affected the commitment of Puskesmas health workers. The higher the perception of the quality of work life of health workers at Puskesmas in East Java, the higher the commitment they have to handle COVID-19.